2013
DOI: 10.1057/9781137290717
|View full text |Cite
|
Sign up to set email alerts
|

Fraud, Corruption and Sport

Abstract: Palgrave Macmillan is the global academic imprint of the above companies and has companies and representatives throughout the world.Palgrave® and Macmillan® are registered trademarks in the United States, the United Kingdom, Europe and other countries.This book is printed on paper suitable for recycling and made from fully managed and sustained forest sources. Logging, pulping and manufacturing processes are expected to conform to the environmental regulations of the country of origin.A catalogue record for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 0 publications
0
35
1
Order By: Relevance
“…This is consistent with Chiweshe (2014), that referees are playing a major role in expansion ing sports corruption practices in African football, in which referees and linesmen are bought by air from all over Africa and Europe specially to disrupt games. This is also assured with Brooks et al (2013), that referees conspire to manipulate football matches' results in order to obtain illegal payments, and this what causes majority of damages occurred in football integrity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with Chiweshe (2014), that referees are playing a major role in expansion ing sports corruption practices in African football, in which referees and linesmen are bought by air from all over Africa and Europe specially to disrupt games. This is also assured with Brooks et al (2013), that referees conspire to manipulate football matches' results in order to obtain illegal payments, and this what causes majority of damages occurred in football integrity.…”
Section: Discussionmentioning
confidence: 99%
“…It also showed that sports organizations recognized that "sports fraud" should be described as a criminal offense specified in national legislation across Europe, beside the necessity of sports organizer's right in betting revenues as a source of football financing. Brooks et al (2013), aimed to identify types of fraud and corruption within commercial era of "modern" football in the international context, which indicated that tickets that are sold at market price instead of ticket's actual face value comes at the forefront of sports corruption types, in addition to illegal websites that take advantage of market gaps to disappear before police do anything with them. This study also showed that football agents dodging from paying the fees and potential taxes and also dodging from having a license, those were the most obvious corruption methods.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Italian soccer offers a quintessential example. Brooks et al, (2013) highlight that in 2006, a number of prominent clubs in the top division of Italian soccer, notably champions Juventus, were implicated in a scandal that has become known as Calciopoli (Football City). Five clubs were accused by prosecutors of the Italian soccer association of rigging games by selecting referees considered favorable to their clubs and therefore officiating to the advantage of their respective teams.…”
Section: Fairness Fixing and Fundingmentioning
confidence: 99%
“…This assertion has been reinforced by the scholarly community (see Di Ronco & Lavorgna, 2014;Harberfeld & Sheehan, 2013;Hill, 2010Hill, , 2013Hill, , 2015. Furthermore, Eaton postulated that although match-fixing was still driven by sporting factors (i.e., the pursuit of promotion and avoidance of relegation), this motivation had been eclipsed by financial incentives linked to gambling (see Brooks et al, 2013). To an extent this has been epitomized by soccer and its match-fixing travails over the past decade (Di Ronco & Lavorgna, 2014;Hill, 2010Hill, , 2013Hill, , 2015Manoli & Antonopoulos, 2014).…”
Section: Fairness Fixing and Fundingmentioning
confidence: 99%